Ecumenical Solidarity: the World Council of Churches’ Programme to Combat Racism and the Support of the Evangelical Church in Hesse and Nassau - Abuom, Agnes (The ecumenical review, 2021)
In October 1970, the synod of the Evangelical Church in Hesse and Nassau agreed to support the Special Fund of the Programme to Combat Racism (PCR) of the World Council of Churches from church tax contributions. The church was the first regional Protestant church in West Germany to offer financial support to the Special Fund of the PCR, at a time when the programme was facing heavy criticism in the Federal Republic of Germany. This article is an edited version of a video address to a special session of the Evangelical Church in Hesse and Nassau synod on 26 November 2020 to commemorate the 1970 decision of the church.